LINGUISTIC AND CULTURAL ASPECTS OF FOLK JOKES (ON THE EXAMPLE OF UZBEK, RUSSIAN AND ENGLISH LANGUAGES) - Qalandarova, Vazira (Журнал иностранных языков и лингвистики, 2023)
This work examines the texts of Uzbek jokes based on journalistic materials, their composition with the rationale for their brevity, followed by an analysis of linguistic units. Among the anecdotes studied, the author singles out universal, primordially national ones, in which the comic effect of the language is created due to linguistic units (metaphors, hyperbole, comparisons, etc.).